Advertising and public relations in the tourist promotion of the Costa Blanca Board. 2008-2010 - Fernández Poyatos, María Dolores; Aguirregoitia Martínez, Ainhoa (Historia y Comunicación Social, 2014)
The Costa Blanca Board, the public body responsible for the management of tourism in the province of Alicante, is in charge of formalising the promotion, in which tourist communication (advertising and public relations) takes a prominent place. The objective of this research is to understand and appreciate its communication strategies between 2008 and 2010. After the analysis, we note the lack of broaded strategic plans of communication, where the medium and long term can be taken into account and, also, where effectiveness of the programs developed and actions used can be determined.